(untitled) (International journal of artificial intelligence, 2025)
The publicistic style in the Arabic language is understood as the collection of linguistic tools used to cover urgent issues in social life, as well as political, social, economic, and cultural events. This style is primarily used in mass media outlets: newspapers, magazines, radio, television, and internet publications. This article discusses the genres and types of this style.